Staff-Student Exchange between MMIHS and Bournemouth University (UK) - Marahatta, S.; Regmi, P.; Knight, A.; Kuncova, J.; Asbridge, E.; Khanal, D.P.; van Teijlingen, E. (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
The world is rapidly becoming a smaller place with globalisation occurring everywhere. The process of internationalising higher education institutions through partnerships like ours, brings benefits to both MMIHS and BU and to both staff and students. For the latter, it offers new ideas, alternative ways of thinking, insights in the other people’s value systems and cultures, etc. It equips students and staff with knowledge, skills and dispositions to work in culturally diverse and international contexts, providing them with a wider diversity of knowledge and greater understanding of global issues and challenges. In short, the partnership offers many opportunities to gain new experiences, explore new sources and perspectives, and improve their cross-cultural capabilities and, ultimately, their employability